SP 2. Pallidal low frequency activity correlates with dystonic symptoms in patients with cervical dystonia. Issue 9 (September 2016) - Neumann, W.-J.; Huebl, J.; Brücke, C.; Slentz, C.; Schneider, G.-H.; Kühn, A.A.
Abstract : Question: Low frequency (4–12 Hz) oscillations in the internal pallidum (GPi) have been shown to be correlated and coherent with dystonic EMG activity and have therefore been proposed as a pathophysiological signature in patients with dystonia. The aim of this study was to investigate the potential association between pallidal 4–12 Hz activity and symptom severity as quantified by the Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS) in patients with cervical dystonia. Methods: 27 patients undergoing functional neurosurgery for therapeutic deep brain stimulation targeting the GPi were included in our study. Pallidal local field potentials were recorded bilaterally at rest from adjacent contact pairs (01, 12, 23) of the externalized leads before implantation of the impulse generator. All time-series data were taken to the frequency domain using fourier transform based methods. Resulting power spectra were normalized and visually inspected for peaks in the low-frequency ( θ : 4–12 Hz) and beta band ( β : 13–30 Hz). Additionally, inter-hemispheric coherence as a measure of spatial oscillatory connectivity has been analysed. Spearman's correlations have been conducted to investigate a potential association between coherence and peak amplitude and preoperative dystonic symptom severity (TWSTRS) for each frequency band. Results: All patients had distinct peaks in the low frequency band (4–12 Hz, mean: 6.6 Hz ± 0.26 S.E.M.) and in the beta band (13–30 Hz, mean: 17 Hz ± 0.68 S.E.M.). Both, averaged low frequency peak amplitude across available contact pairs and averaged inter-hemispheric low frequency band coherence correlated significantly with the patients' dystonic symptom severity, as measured by preoperative TWSTRS ( N = 27, Spearman's ρ = 0.39, P = 0.02 and Spearman's ρ = 0.54, P = 0.002 for peak amplitude and coherence respectively) and the correlation got better when only the highest peak amplitude was chosen in each electrode ( N = 27, Spearman's ρ = 0.47, P = 0.006). None of the correlations were significant for the beta band peak amplitudes, nor the beta band coherence. Conclusions: The results of our study suggest that pallidal low frequency oscillations have a functional role in the pathophysiology of dystonia and may be a biomarker for dystonic symptom severity, which could potentially be used for adaptive deep brain stimulation.